A comparison between linear backprojection (transpose) and layergram backprojection methods for image reconstruciton in charged- couple device (CCD) based optical tomography - Idroas, Mariani (Penerbit UTM Press, 2011)
The image reconstruction process for CCD–based optical tomography with four projections is discussed in this paper. The CCD linear image sensor used in the study is a Sony ILX551A which has 2048 pixels with a pixel size of 14-microns. The pixel arrangement used in the system is a combination of octagonal and square pixels to ensure that light passes through the same number of pixel rows on all four projections. Two image reconstruction methods are discussed and compared in the paper – the transpose method and the layergram method. The transpose method involves the multiplication and inversion of matrices while the layergram method is simply the addition of the values of attenuation coefficients. The layergram method was found to produce better images than the transpose method, qualitatively and quantitatively (values of a). However, the transpose method requires a shorter processing time than the layergram method.